Patient-physician discussions about costs: definitions and impact on cost conversation incidence estimates. Issue 1 (December 2016) - Hunter, Wynn; Hesson, Ashley; Davis, J.; Kirby, Christine; Williamson, Lillie; Barnett, Jamison; Ubel, Peter
Abstract Background Nearly one in three Americans are financially burdened by their medical expenses. To mitigate financial distress, experts recommend routine physician-patient cost conversations. However, the content and incidence of these conversations are unclear, and rigorous definitions are lacking. We sought to develop a novel set of cost conversation definitions, and determine the impact of definitional variation on cost conversation incidence in three clinical settings. Methods Retrospective, mixed-methods analysis of transcribed dialogue from 1, 755 outpatient encounters for routine clinical management of breast cancer, rheumatoid arthritis, and depression, occurring between 2010–2014. We developed cost conversation definitions using summative content analysis. Transcripts were evaluated independently by at least two members of our multi-disciplinary team to determine cost conversation incidence using each definition. Incidence estimates were compared using Pearson's Chi-Square Tests. Results Three cost conversation definitions emerged from our analysis: (a) Out-of-Pocket (OoP) Cost – discussion of the patient's OoP costs for a healthcare service; (b) Cost/Coverage – discussion of the patient's OoP costs or insurance coverage; (c) Cost of Illness– discussion of financial costs or insurance coverage related to health or healthcare. These definitions were hierarchical; OoP Cost was a subset of Cost/Coverage, which was a subset of Cost of Illness. In each clinical setting, we observed significant variation in the incidence of cost conversations when using different definitions; breast oncology: 16, 22, 24 % of clinic visits contained cost conversation (OOP Cost, Cost/Coverage, Cost of Illness, respectively;P < 0.001); depression: 30, 38, 43 %, (P < 0.001); and rheumatoid arthritis, 26, 33, 35 %, (P < 0.001). Conclusions The estimated incidence of physician-patient cost conversation varied significantly depending on the definition used. Our findings and proposed definitions may assist in retrospective interpretation and prospective design of investigations on this topic.